Examining Marriage and Partnering Practices Among Students in Higher Learning Institutions in Tanzania - Noel Julius Ntawigaya; Festo Kazonda (CV. Samuel Manurung and Co, 2025)
This study explores marriage and partnering practices among university students in Tanzania, focusing on factors influencing cohabitation and the associated challenges impacting academic performance. Data collected from 90 students at two universities in Mbeya revealed that motivations for cohabitation include emotional, social, and financial factors such as feelings of maturity (38.89%), pressure from unplanned pregnancies (45.56%), peer influence (47.78%), and shared financial responsibilities (44.44%). However, cohabitation also presents significant challenges, including unplanned pregnancies (50%), frequent conflicts (53.33%), infidelity (53.33%), social stigma (36.67%), and health risks like infectious disease transmission (23.33%). These challenges negatively affect students' academic engagement, with over half reporting academic distractions (57.67%). The study recommends comprehensive sexual education, accessible counseling services, financial support programs, inclusive environments, health awareness, tailored academic support, and workshops on healthy relationship skills. These initiatives can help institutions create supportive interventions, enabling students to manage cohabitation complexities while promoting academic success and personal development.